1983
DOI: 10.1159/000123535
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing Hormone Secretion Is Enhanced by Pertussis Toxin, Cholera Toxin, and Forskolin

Abstract: Pertussis toxin, cholera toxin and forskolin, all of which can increase adenylate cyclase activity, stimulated luteinizing hormone LH release from cultured rat anterior pituitary cells. Although cellular cyclic AMP and growth hormone were increased rapidly by cholera toxin and forskolin, enhanced LH release occurred significantly later with no change in total radioimmunoassayable LH (i.e., released plus stored). These data suggest that changes in cyclic AMP levels may regulate the tonic availability of releasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…When applied to pituitary cell cultures, it pro motes a massive synthesis of intracellular cAM P and an in tense output of the nucleotide to the medium. Our results accord well with the data recently reported by Cronin et al [4], RMI 12,330 A inhibits the adenylate cyclase activity within plated cells as well as within a pituitary homogenate. On the contrary, SQ 22,536 which inhibits the cyclase in an acellular system is obviously unable to block the cyclic nu cleotide synthesis within cultured cells.…”
Section: Discussionsupporting
confidence: 93%
“…When applied to pituitary cell cultures, it pro motes a massive synthesis of intracellular cAM P and an in tense output of the nucleotide to the medium. Our results accord well with the data recently reported by Cronin et al [4], RMI 12,330 A inhibits the adenylate cyclase activity within plated cells as well as within a pituitary homogenate. On the contrary, SQ 22,536 which inhibits the cyclase in an acellular system is obviously unable to block the cyclic nu cleotide synthesis within cultured cells.…”
Section: Discussionsupporting
confidence: 93%
“…Employing cholera toxin, forskolin and extracytoplasmic adenylate cyclase obtained from the Bordetellci pertussis organism, we found that both basal and GnRH-stimulated LH release is enhanced in the presence of increased cAMP production [26,27], In subsequent studies using cells in a continuous perifusion system, we found that the release of LH is delayed and gradual following application of probes known to enhance cAMP production immediately in contrast to the brisk, immediate rise which occurs in response to GnRH [15]. Taken together, these investigations confirmed a relationship between cAMP and LH secretion separate from any effect on the GnRH receptor and suggested that the failure of some investigators to document this relationship may be at tributable to the experimental time course required to detect the cAMP effect.…”
Section: Discussionmentioning
confidence: 96%